Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s42003-021-01921-9
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-level divergence of copepod glycerol transporters and the emergence of isoform-specific trafficking regulation

Abstract: Transmembrane conductance of small uncharged solutes such as glycerol typically occurs through aquaglyceroporins (Glps), which are commonly encoded by multiple genes in metazoan organisms. To date, however, little is known concerning the evolution of Glps in Crustacea or what forces might underly such apparent gene redundancy. Here, we show that Glp evolution in Crustacea is highly divergent, ranging from single copy genes in species of pedunculate barnacles, tadpole shrimps, isopods, amphipods and decapods to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
(65 reference statements)
4
7
0
Order By: Relevance
“…In the phylogenetic tree inferred for Aqp3‐like, we recovered several ancient duplications in the nodes where a habitat transition occurred. Previous studies have reported independent duplications of Aqp3‐like within chelicerates (Finn et al, 2015), myriapods and copepods (Catalán‐García et al, 2021). However, their results could have been biassed due to the omission of other major arthropod lineages in their inferences.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the phylogenetic tree inferred for Aqp3‐like, we recovered several ancient duplications in the nodes where a habitat transition occurred. Previous studies have reported independent duplications of Aqp3‐like within chelicerates (Finn et al, 2015), myriapods and copepods (Catalán‐García et al, 2021). However, their results could have been biassed due to the omission of other major arthropod lineages in their inferences.…”
Section: Resultsmentioning
confidence: 97%
“…We identified a total of 2303 arthropodan, 1225 molluscan, and 52 onychophoran Aqps (Data S4) after annotating 310 arthropodan, 101 molluscan and four onychophoran genomic data sets. Only some Aqps from a few arthropod species and even fewer mollusc species had been previously annotated as aquaporins (Catalán‐García et al, 2021; Colgan & Santos, 2018; Finn et al, 2015; Stavang et al, 2015). We also report here the first identification of Aqps in the phylum Onychophora.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No aquaglyceroporins were recovered in the A. succinea transcriptome; however, their presence was retrieved in the congeneric A. virens (Sars, 1835) , as well as in the other annelids and invertebrates ( Figure 2 and Figure 3 ) [ 66 , 73 , 75 ]. Their presumed absence may be due to low sequencing depth (e.g., only one sample [ 43 ]) which may have resulted in a limited number of genes recovered in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, many species are recognized as successful invaders worldwide [ 39 , 40 ], disrupting ecosystem functioning in both marine [ 41 ] and freshwater environments [ 42 ]. To date, no study concerning amphipod AQPs has been carried out, and the only reports on the presence of some gene subfamilies have been indirectly addressed in works related to L. salmonis [ 16 , 43 ] but never further explored.…”
Section: Introductionmentioning
confidence: 99%